Peran dan Implementasi Psikologi Manajemen dalam Meningkatkan Efektivitas Pengelolaan Pendidikan - Hafidatul Hasanah; Siti Muannifah; Muhammad Sahrulla; Mu’alimin Mu’alimin (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
As expectations for efficient management of educational institutions increase, management psychology in education has become a major concern. This management approach now prioritizes human factors, including motivation, behavior, and the social interactions that occur within educational institutions, in addition to outcomes. The purpose of this study is to uncover emerging research trends in recent years and to comprehensively investigate the role of management psychology in educational settings. The research questions center on emerging research directions and trends in the current literature, as well as how management psychology can help improve the effectiveness of educational management. The research methodology involved a literature review using data from Publish or Perish and Google Scholar. A total of 17 relevant articles were identified based on the initial search results. Five papers were selected for further review after a screening procedure was conducted to identify papers that met the requirements. Three main themes emerged from the research findings: learning management, fostering a positive work environment, and leadership and decision-making. Overall, these results support the strategic role of management psychology in improving educational standards. Further research is recommended to create a more integrated strategy that leverages technology.